Stability of Alkaloids during Drying Process and Their Effect on Anticoagulating Activity of Uncariae Ramulus Cum Uncis - Lu Zou; Fengyu Lu; Bing Lin; Ying Zhou; Tingting Liu; Yue Sun (Journal of Analytical Methods in Chemistry)
The drying process of Uncariae Ramulus Cum Uncis (URCU), a kind of traditional Chinese medicine, was studied in a scale dryer in laboratory at 65°C. It was observed that the alkaloids content of URCU firstly showed a tendency of increasing and then decreasing after reaching the peak at the 570th minute in the process of constant temperature drying. Moreover, the coagulation time of rabbit determined by test tubes has been adopted to study the effect imposed by the content of alkaloids on the anticoagulating activity of URCU. In addition, the software of Minitab was also utilized to fit the correlation between the content of alkaloids and the anticoagulating activity of URCU. The results obtained demonstrated that anticoagulant activities were available in both rhynchophylline and isorhynchophylline, among which the latter was the stronger one, while procoagulant activity was shown in corynoxeine. The case study can provide a useful reference for the research on drying other Chinese herbal medicines (CHMs) and further study on URCU.